Exploratory analysis of the position of Chinese cities as international tourism hubs: product destination versus business environment internationalization - Xiang Feng; Ben Derudder; Xiaochuan Zhu; Haixia Zhou (Boletín de la Asociación de Geógrafos Españoles)
This paper measures the level of tourism internationalization of 50 major cities in Mainland China by analyzing their connectivity as international tourism hubs. A typology of cities is presented based on a comparison of their ‘product destination internationalization’ and ‘business environment internationalization’ in the tourism sector. Results are interpreted in the context of three dimensions of the internationalization of the Chinese economy: the imbalanced development of the space-economy; the uneven impact of policy plans and mechanisms; and the imprint of spatio-political hierarchies. We discuss how this study can be complemented with research using other spatial imageries, and used as the starting point for further comparative studies on tourism internationalization in other geographical contexts.